A role of Malaysia microfinance institutions on poverty reduction and households’ wellbeing - Noorul Azwin Md Nasir, Noorshella Che Nawi, Nurhaiza Nordin, Nurnaddia Nordin, (Opción, 2019)
This paper is intended to propose a conceptual framework on the role of Malaysian microfinance institutions (MFIs) on poverty reduction and households’ wellbeing. The aim of this paper is to discuss about the conceptual explanation of microfinance and poverty reduction via comparative qualitative method. As a result, paying high interest rates is not a central of concentration among the poor borrower because they borrow funds to become moneylenders, presumably successfully lending at rates higher than their MFI charges. In conclusion, development practitioners still know little about the possible efficiency of microfinance in reducing poverty